Collaterally Sensitive β-Lactam Drugs as an Effective Therapy against the Pre-Existing Methicillin Resistant Staphylococcus aureus (MRSA) Biofilms - Hamna Batool Hashmi; Muhammad Asad Farooq; Muhammad Hashim Khan; Abdulrahman Alshammari; Alanoud T. Aljasham; Sheikh Abdur Rashid; Nauman Rahim Khan; Irum Batool Hashmi; Muhammad Badar; Mohammad S. Mubarak (MDPI AG, 2023)
Methicillin-resistant Staphylococcus aureus (MRSA) is among the leading causes of nosocomial infections and forms biofilms, which are difficult to eradicate because of their increasing resistance to antimicrobial agents. This is especially true for pre-existing biofilms. The current study focused on evaluating the efficacy of three β-lactam drugs, meropenem, piperacillin, and tazobactam, alone and in combination against the MRSA biofilms. When used individually, none of the drugs exhibited significant antibacterial activity against MRSA in a planktonic state. At the same time, the combination of meropenem, piperacillin, and tazobactam showed a 41.7 and 41.3% reduction in planktonic bacterial cell growth, respectively. These drugs were further assessed for biofilm inhibition and removal. The combination of meropenem, piperacillin, and tazobactam caused 44.3% biofilm inhibition, while the rest of the combinations did not show any significant effects. Results also revealed that piperacillin and tazobactam exhibited the best synergy against the pre-formed biofilm of MRSA, with 46% removal. However, adding meropenem to the piperacillin and tazobactam combination showed a slightly reduced activity towards the pre-formed biofilm of MRSA and removed 38.7% of it. Although the mechanism of synergism is not fully understood, our findings suggest that these three β-lactam drugs can be used in combination as very effective therapeutic agents for the treatment of pre-existing MRSA biofilms. The in vivo experiments on the antibiofilm activity of these drugs will pave the way for applying such synergistic combinations to clinics.